Endophytic bacteria in Camellia reticulata pedicels: isolation, screening and analysis of antagonistic activity against nectar yeasts - Meng, Qingxin; Huang, Rong; Xun, Lijie; Wu, Xiaoman; Deng, Shangkao; Yue, Dan; Zhao, Wenzheng; Dong, Xia; Gong, Xueyang; Dong, Kun (Frontiers in Microbiology, 2024)
Camellia reticulata, an ancient plant species endemic to Yunnan Province, China, remains underexplored in terms of its endophytic bacterial communities. The plant tissue pedicel serves as the connection between the flower and the stem, not only delivers nutrients but also transmits metabolic substances from endophytic bacteria to the nectar during long-term microbial colonization and probably improves the antagonistic activity of nectar against yeast. Hence, 138 isolates of endophytic bacteria have been isolated in this study from the pedicels of 12-and 60-year-old C. reticulata. Comparative analysis revealed significantly higher density of endophytic bacteria in older trees. Among these isolates, 29 exhibited inhibitory effects against nectar yeasts. Most of the isolates displayed positive results for Gram staining, catalase reaction, gelatin liquefaction, and motility. Additionally, the isolates demonstrated the ability to utilize diverse substrates, such as glucose, nitrate, and starch. Based on 16S rRNA molecular biology analysis, these isolates were identified to be 11 different species of 6 genera, with the majority belonging to Bacillus genus. Notably, C1 isolate, identified as Bacillus spizizenii, exhibited strongest antagonistic effect against three yeasts, i.e., Metschnikowia reukaufii, Cryptococcus laurentii, and Rhodotorula glutinis, with minimum inhibitory concentration values below 250 µg/mL. Major metabolites of B. spizizenii were aminoglycosides, beta-lactams, and quinolones, which possess antimicrobial activities. Furthermore, KEGG enrichment pathways primarily included the synthesis of plant secondary metabolites, phenylpropanoids, amino acids, alkaloids, flavonoids, neomycin, kanamycin, and gentamicin. Therefore, antagonistic activity of B. spizizenii against yeasts could be attributed to these antibiotics. The findings highlight the diverse endophytic bacteria associated with C. reticulata, indicating their potential as a valuable resource of bioactive metabolites. Additionally, this study provides new insights into the role of endophytic bacteria of pedicels in enhancing nectar resistance against yeasts.